2009
DOI: 10.1038/jcbfm.2009.221
|View full text |Cite
|
Sign up to set email alerts
|

The PPAR-γ Agonist, Darglitazone, Restores Acute Inflammatory Responses to Cerebral Hypoxia–Ischemia in the Diabeticob/obMouse

Abstract: Diabetes is an increased risk factor for stroke and results in increased brain damage in experimental animals and humans. The precise mechanisms are unclear, but our earlier studies in the db/db mice suggested that the cerebral inflammatory response initiating recovery was both delayed and diminished in the diabetic mice compared with the nondiabetic db/ + mice. In this study, we investigated the actions of the peroxisome proliferator-activated receptor (PPAR)-c agonist darglitazone in treating diabetes and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 46 publications
(84 reference statements)
2
47
0
Order By: Relevance
“…Given that stroke is the leading cause of disability and that the obesity epidemic is on the rise these clinical and social problems are expected to get worse, and therefore early interventions are necessary. While experimental studies in genetic or diet-induced obesity models have shown increased cerebral infarct size and poor outcomes of stroke (7,25,32,33,41), the early impact of a high-fat diet (HFD) before the development of obesity on AIS injury and functional outcomes is not known.It is known that the brain relies heavily on constant blood flow for proper function. Two important mechanisms that contribute to the regulation of cerebral blood perfusion are autoregulatory behavior of cerebral vessels and functional hyperemia upon increased neuronal activity (11,16,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that stroke is the leading cause of disability and that the obesity epidemic is on the rise these clinical and social problems are expected to get worse, and therefore early interventions are necessary. While experimental studies in genetic or diet-induced obesity models have shown increased cerebral infarct size and poor outcomes of stroke (7,25,32,33,41), the early impact of a high-fat diet (HFD) before the development of obesity on AIS injury and functional outcomes is not known.It is known that the brain relies heavily on constant blood flow for proper function. Two important mechanisms that contribute to the regulation of cerebral blood perfusion are autoregulatory behavior of cerebral vessels and functional hyperemia upon increased neuronal activity (11,16,20).…”
mentioning
confidence: 99%
“…Given that stroke is the leading cause of disability and that the obesity epidemic is on the rise these clinical and social problems are expected to get worse, and therefore early interventions are necessary. While experimental studies in genetic or diet-induced obesity models have shown increased cerebral infarct size and poor outcomes of stroke (7,25,32,33,41), the early impact of a high-fat diet (HFD) before the development of obesity on AIS injury and functional outcomes is not known.…”
mentioning
confidence: 99%
“…Furthermore, development of hypertension was correlated with these reported changes (Osmond et al, 2009). The 2010 and 2011 studies by Kumari et al in diabetic ob/ob and db/db mice revealed increased matrix metalloprotease (MMP)-9 mRNA, protein and gelatinolytic activity, increased degradation of occludin and collagen IV, a subsequent breakdown of the BBB, and greater infiltration of macrophages into the brain parenchyma (Kumari et al, 2010;. In the recent study by Li et al (2013), the authors reported impaired dilation of small arterioles, altered contraction and dilation of basilar arteries after ischemic injury, and impaired functional hyperemia in the high fat diet-fed rats.…”
Section: Animal Studies: Vascular Changes Due To a High Fat Diet And mentioning
confidence: 90%
“…For example, increased cerebral infarct size and poor outcomes of stroke have been observed in a number of genetic and DIO models subsequently induced with ischemia. These studies included models of DIO via administration of a high fat diet (36% fat; high in saturated fat) for 10 weeks (Deutsch et al, 2009), administration of a 'Western Diet' for 12 weeks (Langdon et al, 2011), administration of a high fat diet (45% fat) for 8 weeks (Li et al, 2013), TallyHo mice (a model of type II diabetes) (Didion et al, 2007), the ob/ob mouse (Mayanagi et al, 2008;Kumari et al, 2010), the diabetic db/db mouse (Vannucci et al, 2001), and the obese Zucker rat (Osmond et al, 2009;. In the 2009 study by Deutsch et al, the authors found that the middle cerebral arteries (MCAs) from obese rats had smaller lumens and thicker walls.…”
Section: Animal Studies: Vascular Changes Due To a High Fat Diet And mentioning
confidence: 99%
“…Obesity is one predisposing factor for acute ischemic stroke [15,16]. In addition, obesity beginning in childhood decreases cerebral vascular function and exacerbates the damage caused by focal ischemia [3,6,7,17,18]. However, obesity does not cause any significant effects on neuronal cell death or survival after global cerebral ischemia [19][20][21].…”
Section: Introductionmentioning
confidence: 98%